Investment in Infrastructure and Regional Growth in China. Issue 9 (14th July 2020) - Jiang, Yanqing; Jiang, Yunliang; Zheng, Jinghai
ABSTRACT: In this paper we empirically examine the possible effects of regional infrastructure investment on regional per capita income growth and regional total factor productivity (TFP) growth. We first present a theoretical framework for output decomposition and then design a panel data growth model to examine the possible impact of regional infrastructure investment on regional per capita income growth. We find a negative effect of the former on the latter. We also perform a variance decomposition exercise and examine the possible effect of regional infrastructure investment on regional TFP growth. Our results suggest that regional infrastructure investment does not affect regional economic growth through the former's impact on regional TFP growth. We also examine the possible relationship between regional infrastructure investment and the estimated individual region effects and find a negative correlation between the two.